The metabolic syndrome and its components are differentially associated with chronic diseases in a high‐risk population of 350 000 adults: A cross‐sectional study. Issue 4 (28th January 2019) - Rayyan Assi, Hana'a; Ziv, Arnona; Dankner, Rachel
Abstract: Aims: We compared strengths of associations conferred by the metabolic syndrome (MetS) and its components across four chronic disease categories (cancer, cardiovascular diseases [CVDs], chronic kidney disease [CKD], and chronic obstructive pulmonary disease [COPD]) in a community‐dwelling high‐risk population. Methods: This is a cross‐sectional analysis of Israeli adults insured in a single health maintenance organization during 2010 to 2013 and having greater than or equal to two MetS components (hypertension, dysglycemia, low high‐density lipoprotein level, high plasma triglyceride level, and obesity). Data regarding MetS components, chronic disease prevalence, and sociodemographic variables were retrieved from electronic health records and disease registries. Results: Among 347 244 eligible members, 54.2% had MetS. MetS was negatively associated with cancer, (prevalence ratio [PR] = 0.86; 95% confidence interval, 0.79‐0.93) and positively associated with CKD (PR = 1.07, [1.01‐1.13]). Some MetS components conferred different associations across the chronic diseases: a high triglyceride level was positively associated with cancer (PR = 1.15, 1.12‐1.18) and CKD (PR = 1.37, 1.32‐1.41) but negatively associated with CVD (PR = 0.88, 0.86‐0.90) and COPD (PR = 0.93, 0.88‐0.98). In the presence of MetS, those with dysglycemia had higher cancer prevalence than those with normoglycemia (PR‐interaction MetS*dysglycemia on cancer = 1.14, 1.06‐1.22). Likewise, in the presence of MetS, men were more likely than women to present with CVD (PR‐interaction MetS*sex on CVD = 1.12, [1.05‐1.20]). Conclusions: Prevalences of the MetS and MetS components distribute unequally across four chronic diseases. MetS including dysglycemia may warrant screening for cancer, and MetS in males may indicate the presence of CVD. Longitudinal studies may reveal if MetS is associated with different risks or merely indicates better prognosis once having a chronic illness.